The Prisca Theologia in the Early Reformation Debates - Tortoriello, Giovanni (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
The paradigm of the prisca theologia, developed by Marsilio Ficino in the second half of the fifteenth century, had a huge influence throughout the early modern period. Its influence on the Reformation debates, however, has not yet been investigated. In the present article, I make an initial contribution to filling this gap. In the first part, I show that theprisca theologia was widely disseminated in the territories of the Holy Roman Empire at the beginning of the sixteenth century, including at the University of Erfurt where Martin Luther was educated. In the second half, I focus on two figures central to the Reformation debates: Johann Eck and Martin Luther. As I show, Eck had an ambivalent attitude towards theprisca theologia: on the one hand, he aimed to reconcile the scholastic tradition with the ancient doctrines of theprisci theologi; on the other hand, he distanced himself from the Hermetic and magical implications of theprisca theologia. Luther, meanwhile, developed an anti-paradigm to Ficino’s prisca theologia: he argued that the improper mixing of black and white magic was born in Persia and then developed in Egypt and Greece.